Effects of 14-week swimming training program on the psychological, hormonal, and physiological parameters of elite women athletes - Santhiago, V.; da Silva, A. S. R.; Papoti, M.; Gobatto, C. A. (The Journal of Strength and Conditioning Research, 2011)
The purpose of the study was to investigate the influence of a 14-week swimming training program on psychological, hormonal, and performance parameters of elite women swimmers. Ten Olympic and international-level elite women swimmers were evaluated 4 times along the experiment (i.e., in T1, T2, T3, and T4). On the first day at 8:00 am, before the blood collecting at rest for the determination of hormonal parameters, the athletes had their psychological parameters assessed by the profile of mood-state questionnaire. At 3:00 am, the swimmers had their anaerobic threshold assessed. On the second day at 3:00 am, the athletes had their alactic anaerobic performance measured. Vigor score and testosterone levels were lower (p = 0.05) in T4 compared with T3. In addition, the rate between the peak blood lactate concentration and the median velocity obtained in the alactic anaerobic performance test increased in T4 compared with T3 (p = 0.05). For practical applications, the swimming coaches should not use a tapering with the present characteristics to avoid unexpected results.